Effect of intensive lifestyle intervention on the association between weight variability and major adverse cardiovascular events in overweight or obese adults with type 2 diabetes mellitus. Issue 3 (3rd January 2023) - Zhong, Xiangbin; Xu, Xingfeng; Liu, Menghui; Wang, Peng; He, Lixiang; Christopher, Odong; Zhang, Shaozhao; Lin, Yifen; Huang, Yiquan; Xiong, Zhenyu; Zhuang, Xiaodong; Liao, Xinxue
Abstract: Aims/introduction: Weight variability is associated with cardiovascular outcomes in diabetic patients. However, whether the guideline‐recommended intensive lifestyle intervention (ILI) will affect this association in overweight or obese adults with diabetes is not well established. Materials and Methods: In 3, 859 participants from the Action for Health in Diabetes (Look AHEAD) trial, the associations of 4 year weight variability measured by variability independent of the mean (VIM) with major adverse cardiovascular event (MACE) and secondary outcomes in ILI and diabetes support & education (DSE) arm were evaluated. Results: During a median follow‐up of 9.6 years, 255 (12.9%) participants in the ILI arm and 247 (13.2%) participants in the DSE arm developed MACE. Participants with the highest quartile of weight variability (VIM Q4) experienced a 2.23‐fold higher risk of MACE compared with the lowest quartile (VIM Q1) in the DSE arm (hazard ratio [HR] 2.23; 95% CI 1.51–3.30). Compared with the lowest weight variability (VIM Q1), participants with the highest weight variability (VIM Q4) were associated with higher risks of secondary cardiovascular composite outcome (HR 1.88; 95% CI 1.20–2.95), all‐cause mortality (HR 3.19; 95% CI 1.75–5.82), and myocardial infarction (HR 1.95; 95% CI 1.12–3.37) in the DSE arm. Conclusions: Among the overweight or obese individuals with type 2 diabetes mellitus, rising weight variability was independently associated with increased MACE risks in the DSE arm. Therefore, a guideline‐recommended ILI strategy for weight loss should be adopted to improve cardiovascular outcomes without worrying about the effect of weight fluctuations. Abstract : Among the overweight or obese individuals with type 2 diabetes mellitus, rising weight variability was independently associated with increased MACE risks in the DSE arm but not in the ILI arm. Therefore, a guideline‐recommended ILI strategy for weight loss should be adopted to improve cardiovascular outcomes without worrying about the effect of weight fluctuations.